Residual Verb Second in French and Romance - Wolfe, S (Universitat Autònoma de Barcelona, 2022)
This article revisits the classic definition of a Residual Verb Second language in light of evidence from the history of French, which is supplemented with synchronic evidence from the Romance languages. The core proposal is that following the loss of the Verb Second property French has successively lost multiple Verb Second correlates such that the grammar at different stages can be described as ‘more’ or ‘less’ Verb Second, according to the degree of left-peripheral phrasal or head movement permitted. Novel corpus data is presented for Renaissance and Classical French to show that the triggers for such movement become increasingly restricted along micro and nanoparametric grounds. The gradient conception of Residual Verb Second which emerges from the data is also borne out in the Modern Romance languages, which are argued to instantiate multiple points on a typology of Verb Second residues according to the degree of left-peripheral phrasal movement or head movement that they license.